The Activity of the Pseudomonas aeruginosa Virulence Regulator σVreI Is Modulated by the Anti-σ Factor VreR and the Transcription Factor PhoB - Quesada, Jose M.; Otero-Asman, Joaquín R.; Bastiaansen, Karlijn C.; Civantos, Cristina; Llamas, María A. (Frontiers in Microbiology, 2016)
Gene regulation in bacteria is primarily controlled at the level of transcription initiation by modifying the affinity of the RNA polymerase (RNAP) for the promoter. This control often occurs through the substitution of the RNAP sigma () subunit. Next to the primary  factor, most bacteria contain a variable number of alternative  factors of which the extracytoplasmic function group (ECF) is predominant. Pseudomonas aeruginosa contains nineteen ECF, including the virulence regulator VreI. VreI is encoded by the vreAIR operon, which also encodes a receptor-like protein (VreA) and an anti- factor (VreR). These three proteins form a signal transduction pathway known as PUMA3, which controls expression of P. aeruginosa virulence functions. Expression of the vreAIR operon occurs under inorganic phosphate (Pi) limitation and requires the PhoB transcription factor. Intriguingly, the genes of the VreI regulon are also expressed in low Pi despite the fact that the VreI repressor, the anti- factor VreR, is also produced in this condition. Here we show that although VreI is partially active under Pi starvation, maximal transcription of the VreI regulon genes requires the removal of VreR. This strongly suggests that an extra signal, probably host-derived, is required in vivo for full VreI activation. Furthermore, we demonstrate that the activity of VreI is modulated not only by VreR but also by the transcription factor PhoB. Presence of this regulator is an absolute requirement for VreI to complex the DNA and initiate transcription of the PUMA3 regulon. The potential DNA binding sites of these two proteins, which include a pho box and –10 and –35 elements, are proposed.